2017
DOI: 10.1007/s11356-017-9392-8
|View full text |Cite
|
Sign up to set email alerts
|

Does trade openness affect CO2 emissions: evidence from ten newly industrialized countries?

Abstract: This paper examines whether the hypothetical environmental Kuznet curve (EKC) exists or not and investigates how trade openness affects CO emissions, together with real GDP and total primary energy consumption. The study sample comprises ten newly industrialized countries (NICs-10) from 1971 to 2013. The results support the existence of hypothetical EKC and indicate that trade openness negatively and significantly affects emissions, while real GDP and energy do positive effects of emissions. Moreover, the empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(111 citation statements)
references
References 32 publications
13
82
1
3
Order By: Relevance
“…The elasticity of lnY 2 showed that a 1% increase in the quadratic term of income level lowered emissions by −0.326% and −0.325% in model 1 and model 2, respectively, investigating the non-linear nexus between income level and pollution. Our findings on the EKC curve are consistent with Gokmenoglu et al [42], who also evidenced an inverted U-shaped relationship for the agriculture sector, as well as Usman et al [13], who confirmed the EKC hypothesis in the case of India, and Zhang et al [14], who evidenced this relationship for newly industrialized countries. Based on our EKC results, we could safely argue that the higher level of income raised more concerns for environmental protection in Pakistan as people could possibly be demanding a more sustainable environment.…”
Section: Ardl Long-term and Short-term Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The elasticity of lnY 2 showed that a 1% increase in the quadratic term of income level lowered emissions by −0.326% and −0.325% in model 1 and model 2, respectively, investigating the non-linear nexus between income level and pollution. Our findings on the EKC curve are consistent with Gokmenoglu et al [42], who also evidenced an inverted U-shaped relationship for the agriculture sector, as well as Usman et al [13], who confirmed the EKC hypothesis in the case of India, and Zhang et al [14], who evidenced this relationship for newly industrialized countries. Based on our EKC results, we could safely argue that the higher level of income raised more concerns for environmental protection in Pakistan as people could possibly be demanding a more sustainable environment.…”
Section: Ardl Long-term and Short-term Resultssupporting
confidence: 92%
“…The cross-sectional study of Zaman et al [28] confirmed a bell-shaped income-pollution nexus, and their findings supported that sectoral growth and energy use induced emissions over the globe. Zhang et al [14] verified a hypothetical EKC in 10 newly industrialized countries by applying panel cointegration and Granger causality tests. Acheampong [45] successfully confirmed the EKC hypothesis at the global and regional level for 116 countries.…”
Section: Cross-country Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Trade openness (sum of merchandise exports and imports divided by the value of GDP) has been extensively used in recent studies examining the EKC framework, as it yields significant results in empirical analyses (see Kisswani and Harraf [46], Ozatac and Gokmenoglu [47], Zhang and Liu [48], Dogan and Turkekul [49]), Ertugrul and Cetin [15], and Kais and Sami [14]). However, α 4 is expected to have a mixed effect on carbon emissions, as it varies with each country's environmental aspects.…”
Section: Methodsmentioning
confidence: 99%
“…The study follows the model of existing studies such as Avetisyan et al 2010; Cristea et al 2013; Gozgor and Can (2016) and Zhang et al (2017); on the validation of the EKC model. Our model also proposes that trade and transport services in the economy are important determinants of carbon emissions.…”
Section: Methodology and Data Usedmentioning
confidence: 99%